The Museum Profession: Protecting and Promoting Professional Commitments. (April 2016) - Mancino, Susan
Abstract: Throughout their history, museums have performed diverse public services: from preservation, collection, and exhibition, to interpretation, education, and civic engagement. As Stephen E. Weil (2002 ) explains, since the mid‐twentieth century, museums have experienced two major revolutions. First, a revolution in focus from collection‐oriented to visitor‐oriented practices, and second, a revolution in public expectations as museums secured a position within the nonprofit sector (81–82). With competition for public, private, and philanthropic support resting upon measurable results, the evaluation of museums depends upon its ability to "accomplish its purpose" (5). However, the question remains: what is the museum's purpose? Which is the more important: collection and artifact preservation, or public engagement and education? An overview of museum practices reveals a multiplicity of professional tasks distributed among three imperatives: preservation, scholarship, and programming (Weil2002, 11). The competition for resources devoted to each of these imperatives can spark controversy—particularly if museum professionals answer the question of the purpose of museums differently. Organizational communication scholar, Janie M. Harden Fritz, developed a theoretical framework that seeks to respond to such controversies in Professional Civility: Communicating Virtue at Work . This essay considers Fritz's "professional civility" in the context of the American museum sector, lending insight to the question of museum purpose and function.